Knowledge management behavior among practitioners in Malaysia - Mohamed Razi, Mohamed Jalaldeen; Mohd Tamrin, Mohd Izzuddin; Ahmad Dahlan, Abdul Rahman; Mohamad Ali, Noor Azian (School of Computing, Univerisiti Utara Malaysia, 2017)
The main aim of this study is to examine the role of specific organizational climate and individual acceptance factors on knowledge management behavior within an organizational context. A hypothetical conceptual research framework was developed based on knowledge creation theory and previous studies. Data were collected from 74 corporate practitioners in Malaysia using a self-administered online questionnaire. Though the linear regression analysis supports all proposed hypotheses, according to stepwise multiple regressions analysis decentralized decision making structure and Information Technology support emerged as the significant predictors of KM behavior.